Effect of milling time on Co0.5Zn0.5Fe2O4 microstructure and particles size evolution via the mechanical alloying method - Yakubu, Abubakar; Abbas, Zulkifly; Hashim, Mansor; Ahmad, Ahmad Fahad (Scientific Research Publishing, 2014)
Nanocrystalline CoZn-ferrite was fabricated by a high-energy milling method by mixing Fe3O4+CoO+ZnO. The structural properties of the milled powder at different milling times were analysed so to ascertain the diffusion of CoO and ZnO into the tetrahedral and octahedral sites using mechanical alloying method. The effect of mechanical alloying towards particle size was also investigated. The XRD spectra indicated the precursors reacted during milling with the diffusion of ZnO and followed by CoO into their respective crystallographic sites. SEM micrographs showed the agglomeration of powders due to high energy milling and TEM images confirmed that the particles of the materials were of nanosize dimension. In addition, the results show that the grain possesses a single-phase CoZn-ferrite structure in a typical size of ~16–30 nm. The experiment reveals that nanosize CoZn-ferrite can be obtained after the powder is milled for about 8 hours at room temperature. The mechanism and efficiency of the synthesis of the technique are also discussed in this paper.